Photonic-structured fibers assembled from cellulose nanocrystals with tunable polarized selective reflection. (7th June 2018) - Meng, Xin; Pan, Hui; Lu, Tao; Chen, Zhixin; Chen, Yanru; Zhang, Di; Zhu, Shenmin
Abstract: Fibers with self-assembled photonic structures are of special interest due to their unique photonic properties and potential applications in the smart textile industry. Inspired by nature, the photonic-structured fibers were fabricated through the self-assembly of chiral nematic cellulose nanocrystals (CNCs) and the fibers showed tunably brilliant and selectively reflected colors under crossed-polarization. A simple wet-spinning method was applied to prepare composite fibers of the mixed CNC matrix and polyvinyl alcohol (PVA) additions. During the processing, a cholesteric CNC phase formed photonic fibers through a self-assembly process. The selective color reflection of the composite fibers in the polarized condition showed a typical red-shift tendency with an increase in the PVA content, which was attributed to the increased helical pitch of the CNC. Furthermore, the polarized angle could also alter the reflected colors. Owing to their excellent selective reflection properties under the polarized condition, CNC-based photonic fibers are promising as the next-generation of smart fibers, applied in the fields of specific display and sensing.